Bovine digital dermatitis in Victoria, Australia. Issue 10 (8th July 2019) - Hesseling, J.; Legione, A. R.; Stevenson, M.A.; McCowan, C.I.; Pyman, M.F.; Finochio, C.; Nguyen, D.; Roic, C.L.; Thiris, O.L.; Zhang, A.J.; van Schaik, G.; Coombe, J.E.
Abstract : Aims: The objectives of this study were to estimate the prevalence of digital dermatitis (DD) in Victoria, Australia, and to investigate which organisms are consistent with typical DD lesions. The prevalence and causative pathogens of DD are not clear yet in Australia and this paper is one of the first to explore these questions in this country. Methods: Examination and sampling of limbs was undertaken at three knackeries in Victoria, Australia. Limbs were classified as normal (N), active DD‐lesion (A), dried or chronic DD‐lesion (D) or suspected case of DD (S). A total of 823 cows were examined. Six skin biopsies were taken at each knackery, from which DNA was extracted for diversity profiling. Histochemical staining of samples was performed on eight of the skin biopsies. Results: DD was detected in 29.8% of all cows. The prevalence of DD was significantly higher in dairy cows (32.2%) than in beef cows (10.8%). The differential abundance of Treponema ‐species was significantly increased in dried lesions, compared with the normal skin biopsies. Actinobacteria, Proteobacteria, Firmicutes and Tenericutes were found to be significantly different in abundance in the DD lesions compared with normal skin biopsies. Silver staining of samples showed only mild inflammation and in two samples organisms with morphology consistent with Spirochaetes were detected. Conclusions: The calculated prevalence indicates that DD is present in Victoria, Australia. The results of diversity profiling showed that the presence of Treponema ‐species was significantly different between the samples of DD lesions and normal skin.